Ten-day Holy Land Tour: Long-lasting Effects on Protestant Travellers - Sherene J Hattingh (International Journal of Religious Tourism and Pilgrimage)
This qualitative study investigated the long-lasting effects of an average tour to the Holy Land on travellers of the same faith. Data were collected using written interviews, diary entries, observations and communications at least one year after Protestant travellers returned from their planned trip. Thematic analysis was used to analyse the data through the three phases of noting, encoding and then interpreting important aspects. The findings show these faith travellers invested themselves into the trip before, during and after, as part of their committed faith formation. Any faith-based reader would be interested in the results that evidence long-lasting effects for the participants through their actions and behaviours. All participants stated that this trip was a highlight, enhancing their personal connection with God and increasing their involvement in various faith events and activities. Since their return from the trip participants have initiated or contributed to multiple activities such as personal Bible study, storytelling, giving a particular book to others, starting Bible study groups and other personal faith formation behaviours within their work, home and community contexts.